Different dimensions of knowledge in teacher education - a general typification - Birgitte Lund Nielsen (Nordic Journal of Comparative and International Education, 2020)
The paper presents a typology of dimensions of ‘knowledge’ related to teacher education and professional practice. It departs from the observation that this theme is determined in many different ways and as a whole seems very difficult to capture. The purpose is to contribute to further clarification. Three dimensions of teacher knowledge are presented: 1) Ways of handling knowledge, 2) Modes of knowledge, and 3) Knowledge in a content perspective. Referring to the first dimension, it is emphasized that student teachers need to develop both a critical consciousness of knowledge, as well as abilities for enacting knowledge and for constructing knowledge. ‘Enacting knowledge’ includes taking different perspectives and using various types of knowledge to understand and handle a professional situation. ‘Constructing knowledge’ refers, for example, to student teachers researching professional challenges. Dimension 2 focuses on different modes in which teacher knowledge can appear with the subcategories global evidence, local ‘evidence’, and theory and philosophy. Dimension 3 refers to knowledge in a content perspective, with an open list of typical content in teacher education. The potentials and perspectives of this typology are discussed, including examples of how it can be used and also reference to professional knowledge and professionalism.